2012
DOI: 10.4149/bll_2012_158
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of melatonin on lipid peroxidation in various tissues of diabetic rats subjected to an acute swimming exercise

Abstract: Abstract:Background: The present study aimed to explore the effect of melatonin administration on lipid peroxidation in various tissues of rats with streptozocin induced diabetes and subjected to an acute swimming exercise. Methods: The study used 80 adult male rats, which were equally allocated to 8 groups: Group 1, general control; Group 2, melatonin-administered control; Group 3, melatonin-administered diabetic control; Group 4, swimming control; Group 5, melatonin-administered swimming; Group 6, melatonin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
5
1
1
Order By: Relevance
“…In this study, MDA concentration in serum from the FT group was the highest, and was positively associated with intensity of swimming exercise (Figure ). The ratio of FT/CT was 1.78‐fold higher than a previous result reported by Bicer et al, indicating that swimming exercise significantly increased MDA concentration.…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, MDA concentration in serum from the FT group was the highest, and was positively associated with intensity of swimming exercise (Figure ). The ratio of FT/CT was 1.78‐fold higher than a previous result reported by Bicer et al, indicating that swimming exercise significantly increased MDA concentration.…”
Section: Discussioncontrasting
confidence: 67%
“…Bicer et al. demonstrated that melatonin administration prevented an increase in free radical production associated with diabetes and an acute swimming exercise. The authors concluded that melatonin administration may help regulate redox status in exercising diabetics .…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin has been reported to be beneficial in reducing hepatic MDA levels in diabetes. 37,52,54,55 Dias et al and Sirovina et al found quercetin effective in reducing hepatic MDA levels in diabetes. 9,48 Atef and Ezz reported that increased MDA levels in diabetes was reduced by resveratrol administration.…”
Section: Discussionmentioning
confidence: 99%
“…32,41,54 Korkmaz et al and Bicer et al found that GSH levels were significantly increased by melatonin administration. 54,55 Sanders et al reported decreased GSH levels and CAT activity, but increased SOD activity in diabetic conditions. 56 However, Guven et al reported no significant difference between diabetes and control group in hepatic GSH levels.…”
Section: Discussionmentioning
confidence: 99%